(untitled) (Texas Journal of Medical Science, 2023)
The aim of the research is to identify the role of recreation and recreational activities in achieving mental motivation among students of the College of Basic Education and mental motivation among students of the College of Basic Education, and the researcher used the descriptive approach to suit the nature of the research The researcher built a measure of the role of recreational activities in achieving mental )2023/2022( motivation and presented it to the experts. The researcher used the appropriate statistical methods. In the third chapter, the researcher presented and analyzed the results and discussed them from the use of their tables, and then the researcher wrote the conclusions, including that recreational activities have a role In achieving the mental motivation of college students, and this is a positive indicator for students and motivates them to think and stimulate their mental abilities, which makes them reveal their capabilities, capabilities and latent mental abilities. And rewarding students who contribute to distinguished creative recreational activities